Insights into Helicobacter pylori macrolide resistance: a comprehensive systematic review and meta-analysis - Morad Kasani, Safoura; Mofid, Maryam; Navidifar, Tahereh; Golab, Narges; Parvizi, Elnaz; Badmasti, Farzad; Sholeh, Mohammad; Beig, Masoumeh (Frontiers in Microbiology, 2024)
Background: Helicobacter pylori infection is a primary global health concern. However, the widespread use of antibiotics, particularly macrolides such as clarithromycin, has increased resistance among H. pylori strains. This study aimed to investigate the prevalence of macrolide resistance in H. pylori in different world regions.Methods: This systematic literature search was performed using the appropriate search syntax after searching PubMed, Embase, Web of Science, and Scopus databases between May 2015 and December 2023. Statistical analysis was performed using Pooled and random effects model in R and the metafor package.Results: A total of 7768 articles were retrieved. After a thorough evaluation, 155 studies (by 178 reports) were finally eligible for inclusion in this systematic review and meta-analysis.According to the results, the majority of studies (178 reports from 43 countries) assessed clarithromycin susceptibility, with a pooled prevalence of 33.3% and high heterogeneity between studies (I² = 98.57%, p < 0.001). The rate of erythromycin resistance was moderate (22.8%, 10 reports), while azithromycin resistance was 34.4% (4 reports). Subgroup analysis revealed significant differences in the prevalence of resistance based on geographic location, continent, and year of publication. Clarithromycin resistance increased from 29.1% (2015-2019) to 36.5% (2020)(2021)(2022)(2023).Conclusions: This study highlights the critical challenges of macrolide resistance in treating H. pylori infection. The high prevalence and geographic variation underscore the need for tailored treatment strategies based on regional resistance patterns. Furthermore, continuously monitoring resistance trends and investigating contributing factors are essential to optimize treatment.